Prototype Penghitung Pengunjung Otomatis Pada Klinik Idaman As’adiyah Berbasis Arduino Uno dan Sensor PIR - Facthur Miftawan Cahya; Achmad Baijuri; Sunardi (Universitas Islam Raden Rahmat, Malang, 2024)
Efficient visitor management is a crucial aspect of clinic operations. However, most clinics still rely on manual methods for recording visitors, which are prone to errors and inefficiencies. This research was conducted at an ideal clinic, As'adiyah Clinic, located in the Situbondo regency, Banyuputih district. In this clinic, when visitors wish to visit a sick individual, they are required to manually input visitor data, presenting a problem especially when the clinic is overflowing with people, creating lines. To address this issue, we developed a prototype of an automatic visitor counter based on Arduino Uno and PIR sensor for As'adiyah Clinic in Situbondo. Developing a precise and effective monitoring system to count clinic visitors automatically is the goal of this research project.